2010
DOI: 10.1111/j.1600-6143.2010.03016.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Study of Belatacept Versus Cyclosporine in Kidney Transplants from Extended Criteria Donors (BENEFIT‐EXT Study)

Abstract: Recipients of extended criteria donor (ECD) kidneys are at increased risk for graft dysfunction/loss, and may benefit from immunosuppression that avoids calcineurin inhibitor (CNI) nephrotoxicity. Belatacept, a selective costimulation blocker, may preserve renal function and improve long-term outcomes versus CNIs. BENEFIT-EXT (Belatacept Evaluation of Nephroprotection and Efficacy as First-line Immunosuppression Trial-EXTended criteria donors) is a 3-year, Phase III study that assessed a more (MI) or less inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
558
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 506 publications
(589 citation statements)
references
References 43 publications
25
558
1
5
Order By: Relevance
“…As in prior analyses 28, 29, 30, acute rejection was defined as central biopsy–proven rejection that was either clinically suspected for protocol‐defined reasons or clinically suspected for other reasons and treated. A combined end point comprising time to first occurrence of death, graft loss or estimated GFR (eGFR) <20 mL/min per 1.73 m 2 was examined post hoc .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in prior analyses 28, 29, 30, acute rejection was defined as central biopsy–proven rejection that was either clinically suspected for protocol‐defined reasons or clinically suspected for other reasons and treated. A combined end point comprising time to first occurrence of death, graft loss or estimated GFR (eGFR) <20 mL/min per 1.73 m 2 was examined post hoc .…”
Section: Methodsmentioning
confidence: 99%
“…These randomized phase III studies compared two belatacept‐based immunosuppressive regimens (more intense [MI] and less intense [LI]) with CsA‐based immunosuppression in adult kidney transplant recipients. In BENEFIT‐EXT, analyses performed at 1, 3 and 5 years after transplant demonstrated that belatacept‐based immunosuppression was associated with similar rates of patient and graft survival and superior renal function versus CsA‐based immunosuppression; however, rates of acute rejection were numerically higher with belatacept‐based treatment 28, 29, 30.…”
Section: Introductionmentioning
confidence: 99%
“…The comparable rates of acute rejection for belatacept‐based vs CsA‐based immunosuppression were preserved over 10 years: acute rejection rates in the belatacept treatment arms (6%‐7%) were noninferior to that observed in the CsA treatment arm (8%) at 6 months posttransplant in IM103‐100 10. Most acute rejection events in belatacept‐treated patients occur within 6 months of treatment initiation 10, 12, 13. In IM103‐100, most BPAR events in the population at first randomization were reported by month 6 (28 of 41, 68.3%).…”
Section: Discussionmentioning
confidence: 97%
“…The additional dose in BENEFIT and BENEFIT‐EXT was administered on day 4 posttransplant to optimize saturation of CD80/CD86 ligands and blockade of CD28 activation. Despite these caveats, in analyses performed at 1 and 7 years posttransplant, rates of acute rejection were higher for belatacept‐treated vs CsA‐treated patients participating in BENEFIT12, 14, 15 and similar for belatacept‐treated vs CsA‐treated patients participating in BENEFIT‐EXT 13, 16…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation